Efeito imediato da realidade virtual sobre a atividade eletroencefalográfica e eletromiográfica no membro superior parético após acidente vascular encefálico - Dias, Miqueline Pivoto Faria (2018)
Introduction Individuals affected by stroke present a limitation in daily life activities, because the upper limb is the most affected. One of the interventions used to rehabilitate these patients is Virtual Reality (VR), a technique that provides integrated motor and cognitive stimulation for these patients. Objective To evaluate the immediate effect of the virtual reality for the paretic upper limb on central and peripheral excitability in individuals after stroke. Materials and Methods This is a Blind Controlled Randomized Clinical Trial, performed in a single care. Twenty-seven hemiparetic subjects participated in the study; ischemic stroke; time of injury in months G1 (n: 13) 81.76 ± 25.56 and G2 (n = 14) 102.92 ± 24.23; with age of 53.70 ± 12.08, being 15 men and 12 women. They were evaluated through the Mini-Mental; the Modified Ashworth Scale, the Fugl-Meyer Scale, and the National Institutes of Health (NIHSS) Vascular Stroke Scale. The patients were randomized into a control group, with 13 individuals (right hemiparesis: 8 and left hemiparesis: 5) and intervention group with 14 participants (right hemiparesis: 7 and left hemiparesis: 7). The patients in the intervention group underwent four minutes of Virtual Reality training offered by the Xbox through the game Fruit Ninja, which requires active shoulder and elbow movements. The control group performed the same active movements, however without the stimulation of the RV game. The electromyographic evaluation of the anterior deltoid muscles and the biceps brachial of the affected limb were performed with the individuals at rest; in maximal voluntary isometric contraction (MVIC) and during the execution of the active movements in both groups. Electroencephalographic activity at rest and during the proposed activity was also evaluated in both groups. Statistical analysis was used the Shapiro-wilk test and for comparison the independent t test; Mann-Whitney; ANOVA; ANOVA ONE WAY; Friedman; Friedman followed by Wilcoxon and for correlation Spearman Test. Results The central excitability (EEG) evaluation, considering the right channels (HD), statistics differences for the frequency data for the FC6 channel were observed; and for the power data in the AF4 and FC6 channels for the G2-RV group, and F8 for the G1 group. In the left hemisphere (HE) and the affected side (LA) analyzes, there were changes in the neural recruitment pattern for the frequency data in channel F7 and F0 (F7 / F8) for the G2-RV group. In the peripheral excitation (EMG), statistical differences were found in the ingestion for the brachial biceps muscle (BB) (p = 0.000) and anterior deltoid muscle (AD) (p = 0.041), without intergroup alterations. The analysis of the dynamics between central and peripheral excitation in both groups was promoted by the measure that increases central excitability (EEG), increases peripheral excitability (EMG). Regarding the performance of the years between the minutes of execution of the game as a score attributed to each minute, the statistical difference was not observed. Conclusion The training with VR promoted immediate changes in central excitability, with increased neural recruitment mainly in the right hemisphere, for the channels FC6, AF4 and F8, corresponding to the pre-central, primary and frontal motor areas. Modifications in the pattern of the activity of the anterior deltoid muscle and brachial biceps of the paretic upper limb were also observed after VR training. The present study demonstrated a strong and positive correlation between EMG and EEG for the intervention group, without significant changes for the control group.